Method for improving bipolar membrane electrodialysis efficiency
By using PBAEM that blocks hydrogen ions in bipolar membrane electrodialysis, the problem of hydrogen ion leakage is solved, the acid-base concentration and current efficiency are significantly improved, energy consumption is reduced, and more efficient acid-base production is achieved.
Patent Information
- Application Number
- CN202411723102.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-07
AI Technical Summary
During bipolar membrane electrodialysis (BMED), the anion exchange membrane cannot efficiently prevent the leakage of hydrogen ions, resulting in hydrogen ions leaking in the acid chamber, reducing the acid concentration and neutralizing the alkali concentration in some alkali chambers, thereby reducing production efficiency.
Anion exchange membrane that can block hydrogen ions leakage is used to prevent hydrogen ions from migration by using PBAEM that blocks hydrogen ions during bipolar membrane electrodialysis to prevent hydrogen ions from migration, improve acid and base concentration, purity and the current efficiency of the system.
It significantly improves the concentration and purity of acid and alkali products, effectively improves the current efficiency of the BMED system, and greatly reduces the energy consumption of acid and alkali production, achieving more efficient acid and alkali production.
Smart Images

Figure CN119386677A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane technology, and in particular relates to a method for improving the efficiency of bipolar membrane electrodialysis. Background Art
[0002] Salty wastewater is a by-product of industries such as seawater desalination, papermaking, chlor-alkali industry, petrochemical industry, coal chemical industry and natural gas industry. When it contains high concentrations (0.5% to 3.4%) of organic pollutants and inorganic salts (such as sodium chloride and sodium sulfate), it is called "high-salt wastewater". If the components in these wastewaters can be effectively recovered, it will not only help protect natural resources, but also promote sustainable development. With the introduction of the concepts of minimum liquid discharge (MLD) and zero liquid discharge (ZLD), the field of salt wastewater treatment has ushered in a technological revolution. In order to meet the requirements of the new concept, a series of technologies have been developed, such as electrodialysis (ED), reverse osmosis (RO), forward osmosis (FO), bipolar membrane electrodialysis (BMED) and other technologies to treat industrial high-salt wastewater.
[0003] Technologies such as ED, RO and FO will concentrate saline wastewater and treat high-salt wastewater by crystallizing liquid salt into solid salt, but these methods are not economically advantageous. Bipolar membrane electrodialysis (BMED) can better solve this problem. BMED is an emerging electrically driven membrane technology consisting of a bipolar membrane (BPM), an anion exchange membrane (AEM), a cation exchange membrane (CEM) and electrodes. BPM consists of three parts: anion selective layer, cation selective layer and transition layer. Under electric field enhancement, water molecules in BPM dissociate into H + and OH - Since cations and anions cannot pass through the two-layer structure of BPM, the H generated by hydrolysis + and OH - The anions in the feed chamber pass through the AEM and H + Combined to form acid, the cations react with OH via CEM - Combine to form a base, thus converting the salt into an acid and a base.
[0004] In the existing salt wastewater recovery, BMED is considered to be an ideal solution in the field of high-salt wastewater resource utilization due to its technical and economic advantages. However, the application of BMED still faces some challenges: 1. Product purity: In many industrial applications, only by significantly reducing the salt impurities in the product can the product be more valuable. On the one hand, the product purity is affected by the transmission of salt ions through the bipolar membrane. The salt anions from the acid chamber will contaminate the produced base, and vice versa, the salt cations from the base chamber will contaminate the produced acid; in addition, the various cations or anions in the feed chamber pass through the ion exchange membrane to form mixed acid or mixed base, further reducing the purity of the product. 2. Product concentration: The leakage of hydrogen ions from the anion exchange membrane is the main reason for the reduction in product concentration; generally, the ion exchange membrane can selectively allow ions with opposite charges to pass through, while blocking ions with the same charge; however, due to the small radius and other reasons, the mobility of hydrogen ions is much higher than that of other cations, resulting in the inability of the anion exchange membrane to completely block protons; the result is that the hydrogen ions in the acid chamber leak, reducing the concentration of the acid, while the leaked hydrogen ions enter the base chamber and neutralize part of the base, resulting in a decrease in the base concentration.
[0005] The proton leakage behavior of traditional anion exchange membranes is often considered to be the culprit for low current utilization and low acid concentration. Like the perfluorocarbon double-layer membrane of the chlor-alkali membrane process, it is very necessary and important to develop anion exchange membranes that block hydrogen ions. Protons have unique transport phenomena: one is that protons are transported in the form of H 3 O + The form of proton transfer is called the Vehicle mechanism. The other is the hopping transfer of protons along the hydrogen bond network formed by water molecules, which is called the Grotthus mechanism. Water molecules play an important role in this. In order to effectively inhibit proton leakage in anion exchange membranes, researchers have tried a variety of methods, including introducing hydrophobic groups, constructing dense membrane structures, and applying weak bases. For example, Yu et al. developed a hydrogen ion barrier AEM based on PVDF-HFP by cross-linking modification. By introducing tertiary amine groups to reduce water mobility, the sulfuric acid concentration was limitedly increased from 0.2 mol / L to 1.08 mol / L. Jang et al. studied the interaction between oxygen and hydrogen ions in the blocking polyepoxyphenyl ether structure to improve the efficiency of blocking hydrogen ions. By reducing the correlation between dimethyl and protons, the hydrogen ion barrier efficiency of DMPPO reached 72%, showing better hydrogen ion barrier performance. Li et al. coated a layer of weak base functional groups on the strong base AEM substrate as an acid barrier layer, and achieved microphase separation through the difference in hydrophilicity between the main chain and side chain of the membrane, thereby significantly improving the hydrogen ion barrier performance while maintaining a low membrane resistance. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the above-mentioned related art at least to a certain extent.
[0007] To this end, the object of the present invention is to provide a method for improving the efficiency of bipolar membrane electrodialysis, which can solve the problem that in the bipolar membrane electrodialysis (BMED) process, the anion exchange membrane cannot effectively prevent the leakage of hydrogen ions, resulting in the leakage of hydrogen ions in the acid chamber, reducing the acid concentration and neutralizing the alkali concentration in part of the alkali chamber, thereby reducing the production efficiency.
[0008] In order to solve the above-mentioned technical problems, the present invention is achieved as follows:
[0009] An embodiment of the present invention provides a method for improving the efficiency of bipolar membrane electrodialysis, wherein the method uses an anion exchange membrane capable of blocking hydrogen ion leakage during the bipolar membrane electrodialysis process to prevent hydrogen ion migration, increase acid-base concentration and purity, and improve the current efficiency of the system.
[0010] In addition, the method for improving the efficiency of bipolar membrane electrodialysis according to the present invention may also have the following additional technical features:
[0011] In some embodiments, the anion exchange membrane is prepared by:
[0012] Weigh a certain mass ratio of base polymer and carrier, pour into organic solvent to dissolve, stir and ultrasonically degas for a period of time to obtain a uniform and transparent casting liquid, then pour the casting liquid into a leveled membrane mold, evaporate at room temperature for a period of time to obtain a uniform anion exchange membrane.
[0013] In some embodiments, the base polymer is cellulose triacetate; and the carrier is trihexyltetradecylphosphine chloride.
[0014] In some embodiments, the carrier accounts for 30%-70% by mass of the casting solution.
[0015] In some embodiments, the thickness of the anion exchange membrane is 50-200 μm, specifically 62 μm, 102 μm, 155 μm or 190 μm.
[0016] In some of the embodiments, the ratio of the base polymer to the carrier is 6:4, 5:5, 4:6 or 3:7.
[0017] In some embodiments, the system used for the bipolar membrane electrodialysis includes: an anode chamber, an acid chamber, a feed chamber, an alkali chamber, and a cathode chamber;
[0018] A bipolar membrane is provided between the anode chamber and the acid chamber; an anion exchange membrane is provided between the acid chamber and the feed chamber; a cation exchange membrane is provided between the feed chamber and the alkali chamber; and a bipolar membrane is provided between the alkali chamber and the cathode chamber;
[0019] Electrode plates are respectively arranged outside the anode chamber and the cathode chamber, and the two electrode plates are respectively connected to the positive electrode and the negative electrode of the power supply.
[0020] In some embodiments, the feed of the feed chamber is 60 g / L sodium chloride, the feed of the acid chamber is 0.1 mol / L hydrochloric acid, and the feed of the alkali chamber is 0.1 mol / L sodium hydroxide;
[0021] The anode chamber and the cathode chamber are connected, and the feed is 0.3 mol / L sodium sulfate.
[0022] In some of the embodiments, the chamber volume ratio of the anode and cathode chambers, the feed chamber, the acid chamber and the base chamber is 2:2:1:1.
[0023] In some embodiments, the current density during bipolar membrane electrodialysis is 10-30 mA / cm 2 .
[0024] In some embodiments, the feed flow rate during the bipolar membrane electrodialysis process is 10 L / h.
[0025] Compared with the prior art, the present invention has at least the following beneficial effects:
[0026] In the embodiment of the present invention, the method for improving the efficiency of bipolar membrane electrodialysis provided solves the problem of hydrogen ion leakage by using PBAEM that blocks hydrogen ions in bipolar membrane electrodialysis (BMED), thereby significantly improving the concentration and purity of acid and alkali products.
[0027] In the embodiment of the present invention, the method for improving the efficiency of bipolar membrane electrodialysis provided effectively improves the current efficiency of the BMED system, while greatly reducing the energy consumption of acid and alkali production, thereby achieving more efficient acid and alkali production;
[0028] The performance of the PBAEM using the method for improving the efficiency of bipolar membrane electrodialysis of the present invention is comparable to that of imported hydrogen ion barrier membranes (such as ACM), has cost advantages, can achieve domestic substitution, and has broad application prospects, especially in the field of high-salt wastewater treatment.
[0029] Under the same test conditions, the acid concentration of the PBAEM of the present invention reaches 1.85 mol / L, and the alkali concentration reaches 1.90 mol / L, which are 59.5% and 29.3% higher than the traditional anion exchange membrane AMX, 46.8% and 22.6% higher than ASO, and 30.3% and 31.0% higher than AMVN, respectively; the energy consumption of the PBAEM of the present invention is as low as E HCl =1.72kWh / kg, E NaOH=1.54kWh / kg, the current efficiency of acid reaches 67.84%, and the current efficiency of alkali is as high as 66.98%. The energy consumption and current efficiency are better than those of ordinary anion exchange membranes; PBAEM maintains stable performance during long-term operation. After 9 hours of continuous operation, the acid concentration can still reach 3.12mol / L, and the alkali concentration can reach 3.09mol / L.
[0030] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of the principle of a hydrogen ion barrier anion exchange membrane coupled with a bipolar membrane electrodialysis disclosed in one embodiment of the present invention;
[0032] Figure 2 The result of the hydrogen ion barrier anion exchange membrane coupled with bipolar membrane electrodialysis disclosed in one embodiment of the present invention;
[0033] Figure 3 The result of the hydrogen ion barrier anion exchange membrane coupled with bipolar membrane electrodialysis disclosed in another embodiment of the present invention;
[0034] Figure 4 The result of the hydrogen ion barrier anion exchange membrane coupled with bipolar membrane electrodialysis disclosed in another embodiment of the present invention;
[0035] Figure 5 A comparison diagram of the hydrogen ion barrier anion exchange membrane coupled bipolar membrane electrodialysis disclosed in an embodiment of the present invention and various commercial anion exchange membranes coupled bipolar membrane electrodialysis;
[0036] Figure 6 This is a comparison chart of the long-term operation of the hydrogen ion barrier anion exchange membrane coupled bipolar membrane electrodialysis disclosed in an embodiment of the present invention and the commercial anion exchange membrane ACM coupled bipolar membrane electrodialysis.
[0037] Description of reference numerals:
[0038] 1-first electrode plate, 2-anode chamber, 3-first bipolar membrane, 4-acid chamber, 5-hydrogen ion blocking AEM, 6-feed chamber, 7-cation exchange membrane, 8-alkali chamber, 9-second bipolar membrane, 10-cathode chamber, 11-second electrode plate. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] The embodiments of the present invention are described in detail below through specific embodiments and application scenarios in conjunction with the accompanying drawings.
[0041] In order to solve the problem of insufficient product concentration in bipolar membrane electrodialysis (BMED), the present invention provides an innovative application of a hydrogen ion blocking anion exchange membrane (PBAEM) in BMED, which can effectively block the leakage of hydrogen ions by combining the selectivity of the movable carrier in the membrane, the membrane surface resistance, the water content and the expansion rate. On this basis, the BMED process can achieve high current utilization and efficient production of high-concentration acid and alkali under low energy consumption conditions, significantly improving the overall performance and economic benefits of the system.
[0042] See also Figure 1 As shown, in some embodiments of the present invention, a method for improving the efficiency of bipolar membrane electrodialysis is provided, comprising the following steps:
[0043] 1. Preparation of PBAEM with hydrogen ion leakage barrier performance: Weigh a certain mass ratio of base polymer and carrier, pour into organic solvent to dissolve, stir for 5 hours and degas in an ultrasonic machine for 15 minutes, pour the uniform and transparent casting liquid into the leveled film mold, and evaporate at room temperature for 5 hours to obtain a uniform film.
[0044] 2. Build a bipolar membrane electrodialysis structure: Bipolar membrane electrodialysis consists of four bipolar membranes, three cation exchange membranes, and three prepared hydrogen ion blocking PBAEMs. Three repeating units constitute the bipolar membrane electrodialysis structure.
[0045] The hydrogen ion blocking PBAEM is composed of a base polymer and a carrier. The base polymer is cellulose triacetate (CTA) and the carrier is trihexyltetradecylphosphine chloride (Cyphos 101 (C 32 H 68 ClP)). The carrier accounts for 30%-70wt% of the casting solution.
[0046] The hydrogen ion blocking AEM is prepared by a solvent volatilization method, and the thickness of the prepared AEM is 50-200 μm, which can be 62 μm, 102 μm, 155 μm and 190 μm.
[0047] Bipolar membrane electrodialysis is composed of an anode chamber, an acid chamber, a feed chamber, an alkali chamber, and a cathode chamber. Electrode plates are arranged outside the anode chamber and the cathode chamber, respectively connected to the positive and negative electrodes of the power supply. A bipolar membrane is arranged between the anode chamber and the acid chamber, a prepared anion exchange membrane capable of blocking hydrogen ions is arranged between the acid chamber and the feed chamber, a cation exchange membrane is arranged between the feed chamber and the alkali chamber, and a bipolar membrane is arranged between the alkali chamber and the cathode chamber.
[0048] The feed chamber is fed with 60 g / L sodium chloride (NaCl), the acid chamber is fed with 0.1 mol / L hydrochloric acid (HCl), the alkali chamber is fed with 0.1 mol / L sodium hydroxide (NaOH), the anode chamber and the cathode chamber are connected in series, and the feed is 0.3 mol / L sodium sulfate (Na 2 SO 4 ). The chamber volume ratio is: cathode chamber: feed chamber: acid chamber: alkali chamber = 2:2:1:1.
[0049] The current density of bipolar membrane electrodialysis is 10-30mA / cm 2 The flow rate of water in the bipolar membrane electrodialysis experiment was 10 L / h to keep the solution uniform.
[0050] Embodiment 1:
[0051] The base polymer cellulose triacetate and the carrier trihexyltetradecylphosphonium chloride were weighed in a certain mass ratio, dissolved in dichloromethane, stirred for 5 hours, and then ultrasonicated to obtain a uniform and transparent casting solution. Finally, the casting solution was poured into a leveled mold and volatilized for 5 hours to form a uniform film. The ratio of base polymer to carrier was 6:4, 5:5, 4:6, and 3:7 for experiments.
[0052] The membrane properties of the ion exchange membrane prepared above were measured. The measured properties of the anion exchange membrane are shown in Table 1. IEC (Ion Exchange Capacity) is the ion exchange capacity.
[0053] Table 1 Some properties of anion exchange membrane
[0054]
[0055] Since hydrogen ions have a special transport mechanism, the moisture content and expansion rate significantly affect their mobility. As can be seen from Table 1, the moisture content and expansion rate of the anion exchange membrane (PBAEM) prepared in Example 1 are both less than 2%, indicating that the membrane has good stability. As the content of triacetyl cellulose (that is, cellulose triacetate) increases, the expansion rate of the membrane gradually decreases. When the content of triacetyl cellulose reaches 60wt%, the weight of the membrane does not change before and after the test, and the expansion rate is 0. This may be due to the fact that the acetate groups in the molecular structure of cellulose triacetate replace a large number of hydroxyl groups, reducing the number of intermolecular hydrogen bonds and forming a tighter molecular arrangement through the hydrophobicity of the acetate groups. The highly crystalline structure limits the free movement of the molecular chains, making it difficult for the membrane to stretch significantly when absorbing water or swelling, thereby reducing the expansion rate.
[0056] Cellulose triacetate is formed by completely or nearly completely acetylation of the hydroxyl groups of cellulose. The acetate groups replace the original hydrophilic hydroxyl groups, weakening the interaction between the molecule and the water molecules. Therefore, cellulose triacetate exhibits stronger hydrophobicity than unacetylated cellulose derivatives, resulting in a lower water content. In addition, the dense selective layer of cellulose triacetate further reduces the penetration and diffusion of water. The long alkyl chain carrier is also hydrophobic, which reduces the affinity with water. Therefore, the prepared AEM has a lower water content and expansion rate, which effectively inhibits the leakage of hydrogen ions.
[0057] At the same time, as the carrier content increases, the viscosity of PBAEM also increases, limiting the transport of anions in high ion exchange capacity (IEC) AEM. This is also the reason why the ion exchange capacity of AEM decreases when the carrier content reaches 70wt%. The increase in viscosity causes part of the carrier to fall off, thereby reducing the IEC.
[0058] Embodiment 2:
[0059] The AEM prepared in Example 1 was used to perform an acid-base test on a bipolar membrane electrodialysis system using a bipolar membrane electrodialysis test device.
[0060] Bipolar membrane electrodialysis configuration Figure 1 As shown. The bipolar membrane electrodialysis includes an anode chamber 2, an acid chamber 4, a feed chamber 6, an alkali chamber 8 and a cathode chamber 10. The outer sides of the anode chamber 2 and the cathode chamber 10 are respectively provided with a first electrode plate 1 and a second electrode plate 11, that is, a positive electrode plate and a negative electrode plate. The two electrode plates are respectively connected to the positive and negative electrodes of the power supply. A first bipolar membrane 3 is provided between the anode chamber 2 and the acid chamber 4; a hydrogen ion blocking AEM 5 is provided between the acid chamber 4 and the feed chamber 6, that is, an anion exchange membrane capable of blocking hydrogen ions prepared in Example 1; a cation exchange membrane 7 is provided between the feed chamber 4 and the alkali chamber 8; and a bipolar membrane is provided between the alkali chamber and the cathode chamber. The effective area of the membranes used is 64cm 2. Each membrane is separated by a gasket with a thickness of 0.5mm. "BP-AC" ("acid chamber-feed chamber-alkali chamber") constitutes a triplet, and the device can contain three triplets. The electrode chamber is 0.3mol / L sodium sulfate, the acid chamber / alkali chamber feed is 0.1mol / L hydrochloric acid / sodium hydroxide, and the feed simulates the saline wastewater of reverse osmosis with 60g / L sodium chloride. The current density is 20mA / cm 2 .
[0061] Experimental treatment: Take 2 ml samples from the acid chamber, base chamber, and feed chamber every hour. The acid and base samples are measured by titration. The concentration of the solution sample in the acid chamber is titrated with NaOH solution. When titrating the acid in the base solution, phenolphthalein is used as an indicator. The sample in the base chamber is titrated with HCl solution, and the concentration is calculated using bromocresol red as an indicator. The feed reaction degree is measured by a conductivity meter. The end time is when the feed conductivity reaches 5mS / cm. Figure 2 The concentration comparison of acid and base in this embodiment. Among them, 2-a is the concentration of acid and base produced by different ratios of blocking hydrogen ion anion exchange membrane coupled with bipolar membrane electrodialysis, and 2-b is the amount of acid and base produced by different ratios of blocking hydrogen ion anion exchange membrane coupled with bipolar membrane electrodialysis. The highest acid is 1.85mol / L, and the highest base is 1.94mol / L, both of which are produced by the anion exchange membrane with base polymer: carrier = 3:7.
[0062] Embodiment 3:
[0063] According to the ratio of base polymer to carrier in Example 1 of 4:6, anion exchange membranes of different thicknesses were prepared to test the effect of membrane thickness on the production of acid and alkali by bipolar membrane electrodialysis. The membranes with thicknesses of 62 μm, 102 μm, 155 μm, and 190 μm were prepared. The same membrane preparation process as in Example 1 was adopted.
[0064] Some properties of the above membranes were measured. The properties of the anion exchange membranes measured are shown in Table 2.
[0065] Table 2 Some properties of anion exchange membrane
[0066] Anion exchange membrane thickness (μm) <![CDATA[Membrane resistance (Ω·cm 2 )]]> 62 3.66 102 6.94 155 10.9 190 14.14
[0067] As the membrane thickness increases, the membrane resistance also increases significantly. When the thickness increases from 62μm to 190μm, the membrane resistance increases from 3.66Ω·cm2 to 14.14Ω·cm2. This is because the increase in thickness causes the ion transmission distance in the membrane to become longer, and a larger energy barrier needs to be overcome, thereby increasing the membrane resistance. Membrane resistance is a key factor in energy consumption during electrolyte conversion. The smaller the resistance, the lower the energy consumption.
[0068] In addition, the membrane thickness also affects the transmission rate of anions in the feed chamber. Therefore, choosing an anion exchange membrane with appropriate thickness not only helps to reduce energy consumption, but also effectively blocks hydrogen ion leakage.
[0069] Embodiment 4:
[0070] The PBAEM prepared in Example 3 was used to perform a bipolar membrane electrodialysis production acid-base test using a bipolar membrane electrodialysis test device.
[0071] The bipolar membrane electrodialysis configuration and conditions are the same as those in Example 2. The test results are shown in Figure 3 shown.
[0072] in, Figure 3 -a is the concentration of acid produced by bipolar membrane electrodialysis coupled with hydrogen ion anion exchange membranes of different thicknesses, Figure 3 -b is the concentration of alkali produced by bipolar membrane electrodialysis coupled with hydrogen ion anion exchange membranes of different thicknesses, Figure 3 -c is the energy consumption and current efficiency in the process of producing acid and alkali by coupling bipolar membrane electrodialysis with different thicknesses of barrier hydrogen ion anion exchange membranes. As the membrane thickness increases, the concentrations of acid and alkali also increase accordingly. When the membrane thickness is 62μm, the concentration of acid is 1.73mol / L and that of alkali is 1.88mol / L; when the thickness increases to 190μm, the acid concentration reaches 1.88mol / L and the alkali concentration rises to 1.97mol / L. This trend can be attributed to the increased retention time of protons in thick membranes, which effectively reduces proton leakage.
[0073] However, as the membrane thickness increases, the transmission time of Cl- ions also increases, resulting in increased energy consumption and reduced current efficiency ( Figure 3 -c). The energy consumption of acid increased from 1.85kWh / kg to 2.56kWh / kg, and that of alkali increased from 1.71kWh / kg to 2.36kWh / kg. At the same time, the current efficiency of acid decreased from 67.84% to 45.65%, and that of alkali decreased from 66.98% to 45.65%.
[0074] This variation in energy consumption and efficiency suggests that although increasing membrane thickness helps to increase acid and base concentrations, there is a significant trade-off between current efficiency and energy consumption.
[0075] Embodiment 5:
[0076] After comprehensive consideration, the anion exchange membrane with a thickness of 102 μm in Example 3 was selected. The bipolar membrane electrodialysis production acid-base test was carried out. The bipolar membrane electrodialysis configuration was the same as that in Example 2.
[0077] To explore the effect of current density, the current density was 10, 15, 20, and 30 Am / cm 2 . Figure 4The results of the effects of different current densities on acid and alkali production. Among them, 4-a is the concentration of acid produced by blocking hydrogen ion anion exchange membrane coupled with bipolar membrane electrodialysis at different current densities, 4-b is the concentration of alkali produced by blocking hydrogen ion anion exchange membrane coupled with bipolar membrane electrodialysis at different current densities, and 4-c is the energy consumption and current efficiency in the process of acid and alkali production by blocking hydrogen ion anion exchange membrane coupled with bipolar membrane electrodialysis at different current densities. The results show that the current density has little effect on the final acid and alkali concentration, but has a significant effect on the ion transfer rate, energy consumption and current efficiency. With the increase of current density, the energy consumption gradually increases, especially at 30A / m2. The energy consumption of acid increases from 1.72KWh / kg to 5.3KWh / kg, and the energy consumption of alkali increases from 1.54KWh / kg to 4.75KWh / kg. This may be due to concentration polarization and the conversion of part of the electrical energy into Joule heat, resulting in additional energy loss.
[0078] At the same time, the desalination time is significantly shortened with the increase of current density. This is mainly because more water in the bipolar membrane dissociates under high electric field strength, and the dissociation of water is intensified under strong electric field. According to the second Wien effect, the water dissociation in the catalytic layer of the bipolar membrane mainly depends on the applied electric field strength. The increase in current density not only accelerates the dissociation of water, but also increases the migration rate of ions, prompting the salt ions to migrate faster.
[0079] Taking all factors into consideration, the current density of 20A / m2 performed best. Under this condition, the energy consumption increased only slightly, with the energy consumption of acid being 2.03KWh / kg and that of alkali being 1.86KWh / kg, but the desalination time was significantly shortened from 8 hours to 4 hours, showing better efficiency and economy.
[0080] Figure 4 -d shows the curve of voltage change over time at different current densities, showing three stages: a decreasing stage, a stable stage, and an increasing stage. This trend is mainly determined by the conductivity of the membrane stack. In the early stage of the experiment, the voltage drop was due to the decrease in solution resistance. Under the action of the electric field, the water in the middle layer of the bipolar membrane dissociates, and the generated H+ and OH- act as carriers to increase the conductivity of the membrane stack, thereby reducing the voltage. As the experiment continues, the total conductivity of the acid, base, and feed chambers remains unchanged, so the voltage drop remains stable. When the salt solution in the feed chamber almost completely migrates to the acid and base chambers, the conductivity of the membrane stack drops significantly, causing the voltage to rise rapidly, marking the end of the experiment. The experimental results show that the voltage drop increases with the increase of current density, which is consistent with Ohm's law: the higher the current density, the greater the voltage drop.
[0081] As a comparative example, sodium chloride was treated for acid-base production using a commercial anion exchange membrane coupled with bipolar membrane electrodialysis. The difference from Example 2 was that the hydrogen ion barrier anion exchange membrane used was replaced with a standard anion membrane (AMX) produced by ASTOM Co., Ltd. of Japan, a hydrogen ion barrier anion exchange membrane (ACM) produced by ASTOM Co., Ltd. of Japan, a monovalent and divalent separation anion exchange membrane (ASO) produced by Asahi Glass Co., Ltd. of Japan, and a standard anion exchange membrane (AMVN) produced by Asahi Glass Co., Ltd. of Japan.
[0082] Comparative Example 1:
[0083] The bipolar membrane electrodialysis device used is similar to that in Example 1, except for the membrane used. This comparative example is composed of anion and cation exchange membranes and bipolar membranes arranged alternately in sequence to form a "BP-AC" ("acid chamber-feed chamber-alkali chamber") membrane stack configuration. The anion exchange membrane here uses the 102μm PBAEM prepared in Example 3, and the number of repeating units is 3. The anode chamber and the cathode chamber are connected in series, and 500mL of 0.3mol / L sodium sulfate solution is introduced as a strong electrolyte solution; 400mL of 60g / L sodium chloride solution is introduced into the feed chamber of the bipolar membrane electrodialysis membrane stack; 200mL of 0.1mol / L hydrochloric acid and sodium hydroxide are respectively introduced into the acid chamber and the alkali chamber of the bipolar membrane electrodialysis membrane stack. During the experiment, the flow rate of each solution in the membrane stack was 10L / h, constant current operation, and the current density was 20mA / cm 2 , the current is set to 1.28A.
[0084] Figure 5 and Table 3 show the concentration results of the acid chamber and base chamber products.
[0085] Comparative Example 2:
[0086] The bipolar membrane electrodialysis device used is the same as that in Comparative Example 1.
[0087] Using bipolar membrane electrodialysis device such as Figure 1 As shown. The "BP-AC" ("acid chamber-feed chamber-alkali chamber") membrane stack configuration is formed by alternating anion and cation exchange membranes and bipolar membranes. The standard anion membrane (AMX) produced by Japan ASTOM Co., Ltd. has a repeating unit number of 3. The anode chamber and the cathode chamber are connected in series, and 500mL of 0.3mol / L sodium sulfate solution is introduced as a strong electrolyte solution; 400mL of 60g / L sodium chloride solution is introduced into the feed chamber of the bipolar membrane electrodialysis membrane stack; 200mL of 0.1mol / L hydrochloric acid and sodium hydroxide are introduced into the acid chamber and alkali chamber of the bipolar membrane electrodialysis membrane stack, respectively. During the experiment, the flow rate of each solution in the membrane stack was 10L / h, constant current operation, and the current density was 20mA / cm 2 , the current is set to 1.28A.
[0088] Figure 5 is a schematic diagram of the concentration of the acid and base products. Table 3 shows the improvement of PBAEM in acid and base concentration compared with other anion exchange membranes. Table 3 Note: The percentage of acid concentration improvement and base concentration improvement is based on the comparison with PBAEM. PBAEM is used as the benchmark, so the improvement value is "-".
[0089] Comparative Example 3:
[0090] The bipolar membrane electrodialysis device used is the same as that in Comparative Example 1.
[0091] Using bipolar membrane electrodialysis device such as Figure 1 As shown. The "BP-AC" ("acid chamber-feed chamber-alkali chamber") membrane stack configuration is formed by alternating anion and cation exchange membranes and bipolar membranes. The anion exchange membrane adopts anion exchange membrane (ACM) produced by Japan ASTOM Co., Ltd., and the number of repeating units is 3. The anode chamber and the cathode chamber are connected in series, and 500mL of 0.3mol / L sodium sulfate solution is introduced as a strong electrolyte solution; 400mL of 60g / L sodium chloride solution is introduced into the feed chamber of the bipolar membrane electrodialysis membrane stack; 200mL of 0.1mol / L hydrochloric acid and sodium hydroxide are introduced into the acid chamber and alkali chamber of the bipolar membrane electrodialysis membrane stack, respectively. During the experiment, the flow rate of each solution in the membrane stack was 10L / h, constant current operation, and the current density was 20mA / cm 2 , the current is set to 1.28A.
[0092] Figure 5 is a schematic diagram of the concentration of the acid chamber and the base chamber products. Table 3 shows the improvement of PBAEM in acid and base concentration compared with other anion exchange membranes. Table 3 Note: The percentage of acid concentration improvement and base concentration improvement is based on the comparison with PBAEM. PBAEM is used as the benchmark, so the improvement value is "-".
[0093] Comparative Example 4:
[0094] The bipolar membrane electrodialysis device used is the same as that in Comparative Example 1.
[0095] The "BP-AC" ("acid chamber-feed chamber-alkali chamber") membrane stack configuration is formed by alternating anion and cation exchange membranes and bipolar membranes. The anion exchange membrane adopts the monovalent and divalent separation anion exchange membrane (ASO) of Asahi Glass Co., Ltd. of Japan, with a repeating unit number of 3. The anode chamber and the cathode chamber are connected in series, and 500mL of 0.3mol / L sodium sulfate solution is introduced as a strong electrolyte solution; 400mL of 60g / L sodium chloride solution is introduced into the feed chamber of the bipolar membrane electrodialysis membrane stack; 200mL of 0.1mol / L hydrochloric acid and sodium hydroxide are introduced into the acid chamber and alkali chamber of the bipolar membrane electrodialysis membrane stack, respectively. During the experiment, the flow rate of each solution in the membrane stack was 10L / h, constant current operation, and the current density was 20mA / cm 2 , the current is set to 1.28A.
[0096] Figure 5 is a schematic diagram of the concentration of the acid and base products. Table 3 shows the improvement of PBAEM in acid and base concentration compared with other anion exchange membranes. Table 3 Note: The percentage of acid concentration improvement and base concentration improvement is based on the comparison with PBAEM. PBAEM is used as the benchmark, so the improvement value is "-".
[0097] Comparative Example 5:
[0098] The bipolar membrane electrodialysis device used is the same as that in comparative example 1. The anion exchange membrane, cation exchange membrane and bipolar membrane are arranged alternately in sequence to form a "BP-AC" ("acid chamber-feed chamber-alkali chamber") membrane stack configuration. The anion exchange membrane adopts the standard anion exchange membrane (AMVN) of Asahi Glass Co., Ltd. of Japan, and the number of repeating units is 3. The anode chamber and the cathode chamber are connected in series, and 500mL of 0.3mol / L sodium sulfate solution is introduced as a strong electrolyte solution; 400mL of 60g / L sodium chloride solution is introduced into the feed chamber of the bipolar membrane electrodialysis membrane stack; 200mL of 0.1mol / L hydrochloric acid and sodium hydroxide are introduced into the acid chamber and alkali chamber of the bipolar membrane electrodialysis membrane stack, respectively. During the experiment, the flow rate of each solution in the membrane stack was 10L / h, constant current operation, and the current density was 20mA / cm 2 , the current is set to 1.28A.
[0099] Figure 5 is a schematic diagram of the concentration of the acid and base products. Table 3 shows the improvement of PBAEM in acid and base concentration compared with other anion exchange membranes. Table 3 Note: The percentage of acid concentration improvement and base concentration improvement is based on the comparison with PBAEM. PBAEM is used as the benchmark, so the improvement value is "-".
[0100] Table 3 Comparative Example PBAEM and other anion exchange membranes in the concentration of acid and alkali improvement data
[0101]
[0102]
[0103] It can be seen from the experimental results of comparative examples 1-5 that the prepared hydrogen ion barrier anion exchange membrane (PBAEM) exhibits excellent hydrogen ion barrier performance in the bipolar membrane electrodialysis (BMED) process, significantly improving the acid-base generation efficiency. The acid concentration of PBAEM reaches 1.85 mol / L, and the base concentration reaches 1.90 mol / L, which are 59.5% and 29.3% higher than the traditional anion exchange membrane AMX, 46.8% and 22.6% higher than ASO, and 30.3% and 31.0% higher than AMVN, respectively. Compared with the best performing ACM membrane on the market, the acid-base concentration of PBAEM is basically the same. This result shows that PBAEM has excellent application potential in the efficient recovery of saline wastewater and resource utilization.
[0104] Comparative Example 6:
[0105] In order to further explore the hydrogen barrier performance of PBAEM, a bipolar membrane electrodialysis device was used in the same comparative example 1, in which anion and cation exchange membranes and bipolar membranes were arranged alternately in sequence to form a "BP-AC" ("acid chamber-feed chamber-alkali chamber") membrane stack configuration. The anion exchange membrane here is 102μm prepared in Example 3, and the number of repeating units is 3. The anode chamber and the cathode chamber were connected in series, and 500mL of 0.3mol / L sodium sulfate solution was introduced as a strong electrolyte solution; 2L of 60g / L sodium chloride solution was introduced into the feed chamber of the bipolar membrane electrodialysis membrane stack; 200mL of 0.1mol / L hydrochloric acid and sodium hydroxide were introduced into the acid chamber and alkali chamber of the bipolar membrane electrodialysis membrane stack, respectively. During the experiment, the flow rate of each solution in the membrane stack was 10L / h, constant current operation, and the current density was 20mA / cm 2 , the current is set to 1.28A.
[0106] Figure 6 It is a schematic diagram of the concentration of the products in the acid chamber and the alkali chamber.
[0107] Comparative Example 7:
[0108] A bipolar membrane electrodialysis device is used in the same manner as in Comparative Example 1, in which anion and cation exchange membranes and bipolar membranes are arranged alternately in sequence to form a "BP-AC" ("acid chamber-feed chamber-alkali chamber") membrane stack configuration. The anion exchange membrane here uses ACM, and the number of repeating units is 3. The anode chamber and the cathode chamber are connected in series, and 500mL of 0.3mol / L sodium sulfate solution is introduced as a strong electrolyte solution; 2L of 60g / L sodium chloride solution is introduced into the feed chamber of the bipolar membrane electrodialysis membrane stack; 200mL of 0.1mol / L hydrochloric acid and sodium hydroxide are introduced into the acid chamber and alkali chamber of the bipolar membrane electrodialysis membrane stack, respectively. During the experiment, the flow rate of each solution in the membrane stack was 10L / h, constant current operation, and the current density was 20mA / cm 2 , the current is set to 1.28A.
[0109] Figure 6 It is a schematic diagram of the concentration of the products in the acid chamber and the alkali chamber.
[0110] It can be seen from the experimental results of Comparative Examples 6-7 that the prepared hydrogen ion barrier anion exchange membrane (PBAEM) exhibits excellent hydrogen ion barrier performance during long-term operation. When the feed chamber is full of raw materials, the performance degradation caused by salt depletion is avoided. Figure 6 As shown in the figure, after 9 hours of operation, the acid concentration of PBAEM reached 3.12 mol / L and the base concentration reached 3.09 mol / L. Compared with the best performing ACM membrane on the market, the acid and base concentrations of PBAEM remained comparable, showing similar stability.
[0111] This experiment further verified the outstanding performance of PBAEM in bipolar membrane electrodialysis, especially its outstanding stability and durability in long-term continuous operation. PBAEM not only effectively prevents hydrogen ion migration and increases acid and alkali concentrations, but also demonstrates efficient resource recovery capabilities in the process of treating industrial high-salinity wastewater and desalination concentrated water.
[0112] The PBAEM of the present invention has advantages in both performance and cost-effectiveness, breaks through the technical bottleneck of traditional anion exchange membranes, provides a more efficient and stable solution for bipolar membrane electrodialysis technology, and has broad industrial application prospects and potential for domestic substitution.
[0113] Parts of the present invention that are not described in detail may refer to the prior art or are known to those skilled in the art.
[0114] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A method for improving the efficiency of bipolar membrane electrodialysis, characterized in that: The method uses an anion exchange membrane capable of blocking hydrogen ion leakage in a bipolar membrane electrodialysis process to prevent hydrogen ion migration, increase acid-base concentration and purity, and improve the current efficiency of the system.
2. The method for improving bipolar membrane electrodialysis efficiency according to claim 1, characterized in that: The anion exchange membrane is prepared as follows: Weigh a certain mass ratio of base polymer and carrier, pour into organic solvent to dissolve, stir and ultrasonically degas for a period of time to obtain a uniform and transparent casting liquid, then pour the casting liquid into a leveled membrane mold, evaporate at room temperature for a period of time to obtain a uniform anion exchange membrane.
3. The method for improving bipolar membrane electrodialysis efficiency according to claim 2, characterized in that: The base polymer is cellulose triacetate; and the carrier is trihexyltetradecylphosphine chloride.
4. The method for improving bipolar membrane electrodialysis efficiency according to claim 2, characterized in that: The mass percentage of the carrier in the casting solution is 30%-70%.
5. The method for improving bipolar membrane electrodialysis efficiency according to claim 2, characterized in that: The thickness of the anion exchange membrane is 50-200 μm.
6. The method for improving bipolar membrane electrodialysis efficiency according to claim 2, characterized in that: The ratio of the base polymer to the carrier is 6:4, 5:5, 4:6 or 3:
7.
7. The method for improving bipolar membrane electrodialysis efficiency according to claim 1, characterized in that: The system used for the bipolar membrane electrodialysis comprises: an anode chamber, an acid chamber, a feed chamber, an alkali chamber and a cathode chamber; A bipolar membrane is provided between the anode chamber and the acid chamber; an anion exchange membrane is provided between the acid chamber and the feed chamber; a cation exchange membrane is provided between the feed chamber and the alkali chamber; and a bipolar membrane is provided between the alkali chamber and the cathode chamber; Electrode plates are respectively arranged outside the anode chamber and the cathode chamber, and the two electrode plates are respectively connected to the positive electrode and the negative electrode of the power supply.
8. The method for improving bipolar membrane electrodialysis efficiency according to claim 7, characterized in that: The feed of the feed chamber is 60g / L sodium chloride, the feed of the acid chamber is 0.1mol / L hydrochloric acid, and the feed of the alkali chamber is 0.1mol / L sodium hydroxide; The anode chamber and the cathode chamber are connected, and the feed is 0.3 mol / L sodium sulfate; The chamber volume ratio of the anode and cathode chambers, the feed chamber, the acid chamber and the base chamber is 2:2:1:
1.
9. The method for improving bipolar membrane electrodialysis efficiency according to claim 7, characterized in that: The current density during bipolar membrane electrodialysis is 10-30 mA / cm 2 .
10. The method for improving bipolar membrane electrodialysis efficiency according to claim 7, characterized in that: The feed flow rate during the bipolar membrane electrodialysis process was 10 L / h.